1985
DOI: 10.1080/15287398509530638
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of hexachlorobenzene, β‐naphthoflavone, and phenobarbital on cytochrome p‐450 and mixed‐function oxidases in Japanese quail

Abstract: Hexachlorobenzene (HCB), beta-naphthoflavone (BNF), or phenobarbital (PB) was administered to Japanese quail to determine their effects on hepatic porphyrin levels and drug-metabolizing enzymes. While HCB increased porphyrin levels, PB slightly reduced them, and BNF had no effect. HCB was an excellent inducer in quail, increasing the specific content of cytochrome P-450 to levels similar to those produced by BNF. Additional similarities between HCB- and BNF-treated quail included a comparable hypsochromic abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In the present study, the lack of effect of PB treatment on CPR activity in the chicken may be related to the bird-specific sensitivity of microsomal enzymes (including CPR) to PB [50]. Unlike humans or rats, little is known about the effect of β-NF and acetone on CPR in chickens, although β-NF and hexachlorobiphenyl (which is a potent inducer of CYP1 and CYP2B) significantly induced CPR activity in the Japanese quail.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In the present study, the lack of effect of PB treatment on CPR activity in the chicken may be related to the bird-specific sensitivity of microsomal enzymes (including CPR) to PB [50]. Unlike humans or rats, little is known about the effect of β-NF and acetone on CPR in chickens, although β-NF and hexachlorobiphenyl (which is a potent inducer of CYP1 and CYP2B) significantly induced CPR activity in the Japanese quail.…”
Section: Discussionmentioning
confidence: 74%
“…Gupta et al [49] demonstrated that injection of PB (80 mg/kg, i.p., for 4 days) induced the activities of some CYP-related activities in adult hen livers, but did not refer to CPR. Additionally, in Japanese quails, injection of PB (70 mg or 150 mg/kg/day, i.p., for 5 days) resulted in a significant increase in CYP contents, but no change in the level of CPR [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PB had less induction power in quails than in rats (see also [12]; CF increases all the measured microsomal activities after 14 days of treatment but was barely active at 7 days. The effect of inducers on DAO activity, measured using 14C-putrescine as substrate, is more easily understood considering the data of part I.…”
Section: Tablementioning
confidence: 92%
“…We have chosen to use the Japanese quail as a representative for a bird species because some information on hepatic P450 induction for this species is available. For instance, the induction of hepatic P450 activities after treatment of Japanese quail with other organochlorine contaminants [15,16], β‐naphthoflavone and pheno‐barbital [17,18], has been reported.…”
Section: Introductionmentioning
confidence: 99%